Sustainable risk management in the construction industry: lessons learned from the IT industry - Hwang, Bon-Gang; Chen, Meiru (Technological and Economic Development of Economy, 2015)
Risk management is a tool used by the construction industry to reduce cost and time overruns. Its implementation in Singapore has remained low, however. This study aims to draw attention to the lack of risk management implementation and to make recommendations for increasing implementation levels in the Singapore construction industry. To accomplish these objectives, the Information Technology (IT) industry was selected to serve as a comparison group. A questionnaire was developed and distributed to companies in both the IT and construction industries. The results from the study established that practitioners in the IT industry tend to be risk takers who want to be trained and equipped with risk management skills while construction industry practitioners tended to be risk avoiders who resisted the changes required to implement risk management. Also, when compared to the IT industry, the construction industry respondents did not seem to have an adequate understanding of the benefits of risk management. Providing some recommendations for the construction industry, the findings from this study will contribute to increasing awareness of the benefits of risk management and its implementation.